2008
DOI: 10.1143/jjap.47.2704
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Gate Interfacial Resistance on the Formation of Insulative Boron–Nitride for p-Channel Metal–Oxide–Semiconductor Field-Effect Transistor in Tungsten Dual Polygate Memory Devices

Abstract: We investigated the effect of boron at the interface of the diffusion barrier in tungsten polymetal gate stacks on the gate contact interfacial resistance between tungsten and p+ polycrystalline silicon (poly-Si). B-N formation can occur at the bottom of WN, which is a crucial layer for preventing abnormal tungsten silicidation between the tungsten gate electrode and poly-Si. Dissociated nitrogen from the WN layer during postdeposition thermal treatment could easily interact with outdiffused boron, creating an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Figure b summarizes the tensile strength between the BNNs/PVA@FGM and reported BN composites. ,,,,, It could be concluded that our BNNs/PVA@FGM exhibited very competitive mechanical performance. The high thermal conductivity and tensile strength of the BNNs/PVA@FGM composite paper makes it an promising candidate for microelectronics , and high RF devices.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure b summarizes the tensile strength between the BNNs/PVA@FGM and reported BN composites. ,,,,, It could be concluded that our BNNs/PVA@FGM exhibited very competitive mechanical performance. The high thermal conductivity and tensile strength of the BNNs/PVA@FGM composite paper makes it an promising candidate for microelectronics , and high RF devices.…”
Section: Results and Discussionmentioning
confidence: 99%
“…There has long been interest in the chemical vapor deposition of metal boride coatings, owing to their highly attractive properties, such as hardness, infusibility, moderate strength, resistance to wear and corrosion, chemical inertness, and excellent electrical conductivity. In general, metal diborides have considerable potential as diffusion barriers for copper interconnects and as contact metals and gate electrode materials for silicon metal-oxide semiconductor field effect transistors (MOSFETs). …”
Section: Introductionmentioning
confidence: 99%